Critical to Know Pcrit: A Review on Pharyngeal Critical Closing Pressure in Obstructive Sleep Apnea - Kazemeini, Elahe; Van de Perck, Eli; Dieltjens, Marijke; Willemen, Marc; Verbraecken, Johan; Op de Beeck, Sara; Vanderveken, Olivier M. (Frontiers in Neurology, 2022)
It is crucial to understand the underlying pathophysiology of OSA. Upper airway collapsibility is an important pathophysiological factor that affects the upper airway in OSA. The aim of the current paper was to review the existing body of knowledge on the pharyngeal collapsibility in obstructive sleep apnea (OSA). After a thorough search of Medline, PubMed, Scopus and Web of science, the relevant articles were found and used in this review paper. Critical closing pressure (Pcrit) is the gold standard measure of the degree of collapsibility of the pharyngeal airway. Various physiological factors and treatments affect upper airway collapsibility. Recently it has been shown that the baseline value of Pcrit is helpful in upfront selection of therapy options. The standard techniques to measure Pcrit are labor-intensive and time-consuming. Therefore, despite the importance of Pcrit, it is not routinely measured in clinical practice. New emerging surrogates such as finite element modeling or use of peak inspiratory flow measurements during a routine overnight polysomnography, may enable clinicians to have an estimate of the pharyngeal collapsibility. However, validation of these techniques is needed.